Research on improved time difference estimation algorithm based on fourth-order cumulant in UHF PD location. Issue 1 (July 2021) - Zhu, Wenbing; Xu, Wei; Zhou, Jiabin; Xu, Ran; Yi, Feng
Abstract: Ultra-high frequency (UHF) detection technology is a fast-developing method for partial discharge (PD) diagnosis of electrical equipment in recent years. Extracting accurate time difference is the priority for PD location in electrical equipment using UHF technology. An improved time difference estimation algorithm based on fourth-order cumulants was first proposed in this article. It mainly included the following two steps, that is using the "correlation-shift-superposition" transformation method to process multiple samples collected from a PD source at first, and then utilizing the statistical characteristics of the fourth-order cumulant to calculate the time difference. In addition, the accuracy and stability of the improved algorithm and the other three common methods were compared. The calculation results show that the improved time difference estimation algorithm based on the fourth-order cumulant can obtain a more accurate and stable time difference than the other three methods. Improved time difference estimation algorithm based on fourth-order cumulant can approximately meet the requirements for reliable location of PD sources.